Direito, energia e tecnologia: a reconstrução da diferença entre energia e tecnologia na forma da comunicação jurídica - Simioni, Rafael Lazzarotto (Universidade do Vale do Rio do Sinos, 2008)
This research supports the thesis that the difference between energy and technology constitutes a functionally different aspect of communication in society, to which the Law System reacts by establishing ways of communication that make invisible a series of paradoxes. The proposition is to observe the operations of energy and technology as genuine forms of social communication, explicitly how technology arises autopoietically from the operative closure executed for the reference to energy. From this perspective, it is possible to observe that the concept of energy symbolizes the interdependent relationship between the social system and its external environment, which, paradoxally can only be observed through technological means. The observation of energy and technology as auto-referential ways of communication allow us to ask about the contingency of energy's meaning in the different fields of communication in the society. In science, energy's meaning rebuilt itself in terms of the difference between attracti
Keywords: autopoiese; energia; sistema da sociedade; tecnologia; direito; autopoiesis; energy; social system; technology; law; Ciências Sociais Aplicadas